THE IMPACT OF INTERNAL AUDITING IN FINANCIAL PERFORMANCE / AN APPLIED STUDY AT TIKRIT UNIVERSITY - Nisreen Abdullah Bdowey; Mariam Dawod Noman; Nuha Safi Abd; Husam Khudhair Khaleel (Scholar Express Journals, 2025)
This study aims to identify the impact of internal auditing on financial performance at Tikrit University, with the aim of identifying the most significant obstacles to enhancing financial performance in the organization under study. To address the research problem, the study relied on data collected through a questionnaire distributed in the field under study, representing internal auditors at Tikrit University. The study reached a number of conclusions, including that internal auditing plays a significant role in improving financial performance by identifying key strengths and weaknesses. Through this, the organization under study can enhance these strengths and address weaknesses to enhance its financial performance. The study also recommends that the university under study enroll internal auditors in advanced training courses to develop their performance, which will positively impact their performance and the organization's overall financial performance .
Keywords: Internal Audit; Financial Performance; Tikrit University